Agreement between In-Clinics and Virus Neutralization Tests in Detecting Antibodies against Canine Distemper Virus (CDV) - Sara Meazzi; Joel Filipe; Alessandra Fiore; Santina Di Bella; Francesco Mira; Paola Dall’Ara (Viruses, 2022)
Core vaccinations and specific antibody titer evaluations are strongly recommended worldwide by all the vaccination guidelines. Virus neutralization (VN) is considered the gold standard for measuring antibody titer against canine distemper virus, but it is complex and time consuming, and the use of in-clinics tests would allow to obtain quicker results. The aim of this study was to evaluate the agreement of the commercial in-clinics VacciCheck test compared to VN. A total of 106 canine sera were analyzed using both methods. The best agreement was obtained using a protective threshold of ≥1:32. VacciCheck showed 95.5% sensitivity, 87.2% specificity, and 92.5% accuracy. The Cohen’s kappa coefficient between methods was 0.84 (CI 95% 0.73 to 0.95), revealing an optimal agreement between the two methods (p = 0.0073). The evaluation of discordant results reveal that most samples had less than 1.5 dilution difference, and that usually did not affect the classification as protected or non-protected. Results also suggest that, in dubious cases, especially when a protective result is expected, retesting is advisable. In conclusion, VacciCheck may be considered as a reliable instrument that may help the clinician in identifying the best vaccine protocol, avoiding unnecessary vaccination, and thus reducing the incidence of adverse effects.